INTERNALISASI NILAI PENDIDIKAN KARAKTER MELALUI METODE PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DAN PEMBIASAAN MEMBACA AL-QUR’AN UNTUK MENANGKAL PENGARUH KEMAJUAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DI TINGKAT SEKOLAH DASAR - Sarafuddin, Sarafuddin (UNIVERSITAS SLAMET RIYADI, 2019)
This study aims to get a clear picture of (1) Strategies to internalize the value of character education through CTL learning methods and the habit of reading the Qur'an to counteract the development of information and communication technology in 3 Public Elementary Schools and solo high schools, and (2)) The CTL learning method and the habit of reading the Qur'an can counteract the development of information and communication technology in 3 public elementary and private high schools. This study included descriptive qualitative research, with a single fixed case study strategy. Data obtained from: (1) Places and events namely learning activities in 3 Public Elementary Schools and private solo schools ;; (2) Documents, namely documents containing textbooks, methods and learning strategies used by the teacher, and reports on student learning evaluation results, and (3) Informants, consisting of PKn subject teachers, local transportation subject teachers and students in 3 Public Elementary Schools and private solo schools. To obtain data is done by (1) Observation; (2) Document analysis, and (3) In-depth interviews. The targets of this study include; (1) Add insight to teachers in choosing learning methods that can understand students about the development of communication and information, and (2) Provide separate learning methods in an effort to internalize the value of character education to students to counteract the development of information and communication technology using the Contextual Teaching and learning methods Learning (CTL) and the habit of reading the Qur'an.Key words: Character Education, CTL and Reading the Al-Qur'an,